Construction of nomogram based on clinical factors for the risk prediction of postoperative complications in children with choledochal cyst - Lin, Yang; Xu, Xinru; Chen, Shan; Zhang, Ling; Wang, Jianbin; Qiu, Xinyi; Li, Lizhi (Frontiers in Pediatrics, 2024)
Objective In order to develop a prediction nomogram based on clinical factors to assess the risk of postoperative complications in children with congenital choledochal cyst. 2 Methods The clinical data from a total of 131 children who suffered from choledochal cyst resection and Roux-en-Y hepaticojejunostomy in our hospital from January 2016 to December 2022 was retrospectively analyzed. The general information, clinical symptoms, procedure suffered, biochemical indicators, imagine data were recorded. An prolomhation of hospital stay inducing by postoperative complications or a follow-up > 6 months was assessed as the event outcome. The logistics regression analysis were performed to screening for risk factors with statistically significance in inducing postoperative complications. Then with the dataset split into training group and internal validation group, the nomogram for prediction of postoperative complications was developed based on computer algorithm. Also, the receiver operating characteristic (ROC) curve and calibration curve were performed for nomogram verification.Of 131 children, the multivariate logistics regression analysis suggested that age ≤ 2 years (OR, 0.93; 95%CI, 0.15-5.65; p=0.938), type I of Todani classification (OR, 36.58; 95%CI, p=0.005), cyst wall thickness > 0.4 cm (OR, 10.82; 95%CI, 2.88-49.13; p<0.001), with chronic cholecystitis (OR, 7.01; 95%CI, 1.62-38.52; p=0.014), choledochal cyst diameter (OR, 1.01; 95%CI, 0.99-1.03; p=0.370) were predictors associated with the postoperative complications of choledochal cysts. The data were randomly divided into training group (N=92) and internal validation group (N=39) to build the prediction nomogram inclusion of the appeal factors. And the accuracy and discrimination of the model were evaluated by receiver operating characteristic (ROC) curve and calibration curve. The results showed that the nomogram AUC = 0.894 (P<0.001, 95%CI:0.822 ~0.966), validation AUC = 0.844 (P<0.001, 95%CI:0.804 ~0.952), Brier=0.120(P<0.001, 95%CI:0.077 ~0.163), indicative of well stability and calibration of the predictive nomogram. Conclusion The prognosis of congenital choledochal cyst was associated with multi-aspects of clinical factors. Combined with the internal validation, the novel prediction nomogram was suitable for evaluating the individualized risk of postoperative complications of choledochal cyst. The prediction nomogram could provide more accurate strategy of procedure and postoperative follow-up for children with choledochal cyst.